Pendampingan Alat Permainan Edukatif (APE) untuk Meningkatkan Keterampilan Numerasi Siswa SD - Ihsani, Baiq Yuliatin; H, Hilmiyatun; Darmurtika, Linda Ayu; A, Akhmad; Milandari, Baiq Desi (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Numeracy skills include skills in applying number concepts and basic mathematical symbols to solve everyday problems. Basic education emphasizes several aspects that students must master, including cognitive, motor and psychomotor aspects. One of the abilities in the cognitive aspect that students must master is the ability to count. Counting is a part related to managing numbers with a system that includes addition, subtraction, division and multiplication. In order for mathematical skills to develop well, teachers must create a fun learning atmosphere, such as using the Numeration pinwheel game. The Numeration Addition Pinwheel is an educational game that was developed by modifying a pinwheel game that can be rotated with numbers. This game aims to increase students' interest in learning numeracy at SDN 1 Danger, to make it easier for students to solve mathematical problems, this research will apply descriptive methods and use a qualitative approach. Data collection is carried out through observation and documentation. The results of this research are expected to improve students' understanding of the material and mathematical abilities. Thus, the educational game tool, the Numeration Addition Wheel, is expected to improve students' mathematical abilities and learning motivation.